2021
DOI: 10.1177/1932202x21995978
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cognitive and Affective Dimensions of Reading Self-Concept With Reading Achievement in English and Russian

Abstract: This study aimed to evaluate whether cognitive and affective dimensions of reading self-concepts in English and Russian are distinct constructs and to examine whether the relationships among cognitive and affective variables are invariant across gender. A total of 349 tenth-grade Azeri students were selected from 12 schools in Baku, Azerbaijan. This study adapted the Self-Description Questionnaire and Cényelvi mérés for assessment of reading self-concepts and achievements in two foreign languages. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 79 publications
4
6
0
Order By: Relevance
“…Arens et al (2011) revealed that regardless of the high correlations between cognitive and affective dimensions of self-concept, mathematics and language subjects of academic achievement had different correlations with the two components of self-concept. Similar findings of Marsh et al (1999), andArens et al (2011) showed that models would fit better to the data if the two components were separated rather than conflated as there was a higher relationship between achievement with the corresponding domain of self-concept than affective component (cognitive math: r = .61, verbal r = .63; affective math: r = .37, verbal: r = .33; cited in Karimova & Csapó, 2021) Moreover, some studies (Arens et al, 2011(Arens et al, , 2014Marsh & Ayotte, 2003;Marsh et al, 2012) examined the twofold multidimensional structure of self-concept within different countries and cultures. Studying the twofold multidimensional nature of native (Chinese) and nonnative (English) languages, Yang et al (2014) found that Chinese vocational students distinguished between two dimensions of academic self-concept.…”
Section: Separation Of Cognitive and Affective Components Of Self-conceptssupporting
confidence: 69%
See 4 more Smart Citations
“…Arens et al (2011) revealed that regardless of the high correlations between cognitive and affective dimensions of self-concept, mathematics and language subjects of academic achievement had different correlations with the two components of self-concept. Similar findings of Marsh et al (1999), andArens et al (2011) showed that models would fit better to the data if the two components were separated rather than conflated as there was a higher relationship between achievement with the corresponding domain of self-concept than affective component (cognitive math: r = .61, verbal r = .63; affective math: r = .37, verbal: r = .33; cited in Karimova & Csapó, 2021) Moreover, some studies (Arens et al, 2011(Arens et al, , 2014Marsh & Ayotte, 2003;Marsh et al, 2012) examined the twofold multidimensional structure of self-concept within different countries and cultures. Studying the twofold multidimensional nature of native (Chinese) and nonnative (English) languages, Yang et al (2014) found that Chinese vocational students distinguished between two dimensions of academic self-concept.…”
Section: Separation Of Cognitive and Affective Components Of Self-conceptssupporting
confidence: 69%
“…Arens et al (2011) revealed that regardless of the high correlations between cognitive and affective dimensions of self-concept, mathematics and language subjects of academic achievement had different correlations with the two components of self-concept. Similar findings of Marsh et al (1999), and Arens et al (2011) showed that models would fit better to the data if the two components were separated rather than conflated as there was a higher relationship between achievement with the corresponding domain of self-concept than affective component (cognitive math: r = .61, verbal r = .63; affective math: r = .37, verbal: r = .33; cited in Karimova & Csapó, 2021)…”
Section: Separation Of Cognitive and Affective Components Of Self-con...supporting
confidence: 69%
See 3 more Smart Citations